2014
DOI: 10.1016/j.forsciint.2013.11.002
|View full text |Cite|
|
Sign up to set email alerts
|

Inconsistency in 9mm bullets: Correlation of jacket thickness to post-impact geometry measured with non-destructive X-ray computed tomography

Abstract: Copyright and reuse:The Warwick Research Archive Portal (WRAP) makes this work by researchers of the University of Warwick available open access under the following conditions. Copyright © and all moral rights to the version of the paper presented here belong to the individual author(s) and/or other copyright owners. To the extent reasonable and practicable the material made available in WRAP has been checked for eligibility before being made available. Copies of full items can be used for personal research or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Studies using industrial CT scanners, with higher resolution (13 μm) and tube voltage (320 kVp), were able to distinguish between the jacket and core. They showed that the thickness of the jacket layer was ~ 0.3–0.4 mm, which is comparable to the size of only one pixel (0.35 mm) on our clinical CT images [11, 17]. Unfortunately, such industrial scanners are not widely available and are not suited for whole body applications [11].…”
Section: Discussionmentioning
confidence: 85%
“…Studies using industrial CT scanners, with higher resolution (13 μm) and tube voltage (320 kVp), were able to distinguish between the jacket and core. They showed that the thickness of the jacket layer was ~ 0.3–0.4 mm, which is comparable to the size of only one pixel (0.35 mm) on our clinical CT images [11, 17]. Unfortunately, such industrial scanners are not widely available and are not suited for whole body applications [11].…”
Section: Discussionmentioning
confidence: 85%
“…To avoid tissue radiation damage, the X-ray tube voltage in medical CT scanners is limited to 150 kVp. Industrial scanners may use energies up to 320 kVp [ 16 ], but these scanners require the body to be rotated, which makes them unsuitable for PMCT. Moreover, higher X-ray energies may also affect or hamper autopsy findings [ 15 ].…”
Section: The Forensic Triagementioning
confidence: 99%
“…al [12] and Thornby et. al [13] indicated the variation of the ballistic behavior of bullets made by various manufacturers especially with respect to asymmetric thinning of the jacket in regions of pre-impact weakness. The bullets were analyzed via CT, subsequently impacted into a rigid flat plate, and the resulting bullet deformation was re-analyzed [12].…”
Section: Introductionmentioning
confidence: 99%